2019
DOI: 10.1186/s40795-018-0267-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of goiter and its associated factors among primary school children in Chole District, Arsi Zone, Ethiopia: a cross- sectional study

Abstract: Background: Goiter remains one of the major public health problems particularly among young children in economically disadvantaged countries like Ethiopia. The aim of the study was to assess the prevalence of goiter and its associated factors among children aged 6-12 years in Chole district, Arsi Zone, Eastern Ethiopia. Methods: A school based cross-sectional study was conducted in February, 2017 among 422 primary school children in Chole district, eastern Ethiopia. The schools and study subjects were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(36 reference statements)
1
6
1
Order By: Relevance
“…The odds of developing goiter among students who had a family history of goiter were 3-fold higher than those with no family history of goiter. This finding is similar to studies [20][21][22]. Thus, children with family history of goiter imply genetic or hereditary factors may play a great role for causation of goiter [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…The odds of developing goiter among students who had a family history of goiter were 3-fold higher than those with no family history of goiter. This finding is similar to studies [20][21][22]. Thus, children with family history of goiter imply genetic or hereditary factors may play a great role for causation of goiter [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…In 1999, the prevalence of thyroid goiter was 12.45% in the Guangdong coastal area ( 9 ), which was much higher than our present results. The prevalence in our study was also lower than that in India (13.98%) ( 22 ), Pakistan (25.5%) ( 23 ), and Ethiopia (36.6%) ( 24 ). The implementation of universal salt iodization programs has markedly decreased the prevalence of thyroid goiter in Guangzhou.…”
Section: Discussioncontrasting
confidence: 72%
“…Another previous study also reported a correlation between low education and an increased frequency of thyroid goiter ( 23 ). In addition, repeat pregnancies can increase the occurrence of thyroid goiter ( 16 , 24 ). Although the total fertility rate of females was higher in rural areas than urban areas, we did not investigate and compare these factors in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced prevalence of iodine deficiency in the study area is promising. However, iodine deficiency was still a public health problem in some parts of the country [26][27][28]. A study conducted in the Robe district in 2015 showed that 57% of the participants had low UIC and the median UIC was 78 μg/L [29].…”
Section: Discussionmentioning
confidence: 99%